Performance Comparison of Permanent Magnet Vernier Motors and Permanent Magnet Synchronous Motors - Yunjiao Li; Jing Zhao; Jie Fu; Yinliang Xia; Wei Wang; Xiaobei Li (Machines)
Nowadays, motor type plays a significant role in the vehicle performances. This article compares various types of permanent magnet vernier motors (PMVMs) with different shapes of field modulation teeth and different numbers of field modulation poles (FMPs). Based on this, the electromagnetic performance of permanent magnet synchronous motors (PMSMs) and PMVMs is compared. First, the back EMF, air gap flux density, flux density distribution, and torque of PMVMs with different shapes of FMPs are compared. Based on the selected PMVMs, the rated torque and overload capacity of PMVMs with different slot–pole combinations are compared. Subsequently, the comprehensive electromagnetic performance of PMVMs and PMSMs is compared, where the strength and weakness of PMSMs and PMVMs are concluded. Finally, a prototype is manufactured and tested, verifying the correctness and accuracy of the simulation model.